2010
DOI: 10.1007/s10886-010-9813-3
|View full text |Cite
|
Sign up to set email alerts
|

Positions and Stereochemistry of Methyl Branches in the Novel Sex Pheromone Components Produced by a Lichen Moth, Lyclene dharma dharma

Abstract: Female moths of Lyclene dharma dharma (Arctiidae, Lithosiinae) produce three sex pheromone components (I-III), for which we assigned the following novel chemical structures; 6-methyl-2-octadecanone (1) for I, 14-methyl-2-octadecanone (2) for II, and 6,14-dimethyl-2-octadecanone (3) for III. In the Iriomote Islands where the insects were collected, a lure including racemic 1 and 2 attracted the male moths without mixing 3. In this study for further confirmation of the plane structures, the positional isomers wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 24 publications
(39 reference statements)
0
9
0
Order By: Relevance
“…(14), fused-ring comp. (68), and heterocyclic comp. (16) for the terpenes (total 275); hydrocarbons (49), primary alcohols and derivatives (28), secondary alcohols and esters (31), ketones Fig.…”
Section: Database Of Arthropod Semiochemicalsmentioning
confidence: 99%
“…(14), fused-ring comp. (68), and heterocyclic comp. (16) for the terpenes (total 275); hydrocarbons (49), primary alcohols and derivatives (28), secondary alcohols and esters (31), ketones Fig.…”
Section: Database Of Arthropod Semiochemicalsmentioning
confidence: 99%
“…The spectral analysis of several synthetic branched 2-ketones indicated that the 6-methyl-2-ketone with characteristic ions at m/z 113 and 95 (113 À H 2 O) was differentiated from the 4-, 5-, and 7-methyl-2-ketones, but differentiation of the mass spectra of the 13-, 14-, and 15-methyl-2-ketones was difficult. 236 A structural determination of the 3,13-dimethyl pheromone (97) was also conducted using a mass-spectral analysis of the pheromone derivative and some synthetic candidates. 286 By transesterication with KOH in MeOH, the novel ester was converted into the methyl ester (97 0 ), which showed ions at m/z 101 (base peak) and 74, indicating a 3-methyl structure (Fig.…”
Section: Structural Determination Of Natural Pheromonesmentioning
confidence: 99%
“…5 The adults of Lithosiinae are called lichen moths because their larvae mainly feed on lichens. 6,7 Lichen moths are found throughout the world and contribute to the ecosystem of the forest. 8,9 In 2010, the sex pheromone of Miltochrista calamine was identified as (5R,7R)-5-methylheptadecan-7-ol (1a, Figure 1).…”
mentioning
confidence: 99%